Diffusion tensor imaging reveals myocardial architectural differences between porcine and primate hearts with potential implications for cardiac xenotransplantation - Henrik Mulbjerg; Steffen Ringgaard; Peter Agger (Scientific Reports)
Abstract Although pig-to-baboon cardiac xenotransplantation has become increasingly successful, challenges remain in its clinical translation, particularly in addressing xenograft overgrowth. While several causes can be managed through genetic modifications and hemodynamic control, growth persists. Research on myocardial architecture and interspecies variation is limited. This study employs diffusion tensor imaging to probe the orientation of cardiomyocytes and their aggregations and aims to investigate whether these parameters may act as intrinsic factors, contributing to xenograft overgrowth in a setting of extrinsic hemodynamic mismatch. Five pig and five baboon ex-vivo hearts were compared by cardiac diffusion tensor magnetic resonance imaging. Myocardial architecture was assessed by quantifying helical, intrusion and E3-angles in left ventricle, septum and right ventricle. Notable differences were found in E3-angles of the left ventricle. The E3 angle was closer to 0° throughout the baboon myocardium. The epicardial E3-angle differed by -9°, midwall by -17.1°, and endocardial by -23.7° The myocardial architecture observed in baboon hearts may support a greater contractional deformation, potentially reflecting an enhanced contractile potential as compared to the porcine heart. Further ex- and in-vivo investigation of both pre- and post-transplantation animals is warranted to assess the exact functional implications of these myocardial architecture differences.